The Influence of Intrinsic and Extrinsic Factors on Immune System Aging - Badowski, Michael (2014)
Sex and age-matched wild-type and TCR transgenic mice were infected with cytomegalovirus (CMV) at 6 months of age and followed for 12 additional months to examine aging of the immune system. It was found that viral infection of C57Bl/6 mice resulted in accelerated aging of the immune system as shown by a loss of CD8(+)28(+) cells and an accumulation of KLRG1(+) T cells. CMV infection of OT-1 transgenic mice had no influence on immune aging of these mice which nonetheless demonstrated an accumulation of CD8(+)28(−) and KLRG1(+) T cells with time. CD4+ T cells were unaffected in either strain of mice. Thus, immunological aging was found to be due to both cell-intrinsic and cell-extrinsic factors. Persistent viral infections may accelerate immunological aging but consideration must be given to individual variation in the aging process.